Color Atlas of pathology
Ilustrated with 1032 figures in color on 343 plates. Endocrine system, including:pituitary,thyroid,parathyroid, adrenals and pancreas.Gynecology and obstetrics, including reproductive organs; Breasts, male genital tract. Skin.